Sedimentary evolutionary processes, architecture, and sedimentary model of a lobate shallow-water delta: insights from flume simulation experiments - Qi, You; Wang, Youjing; Qin, Guosheng; Song, Yanchen; Zhang, Hualing; Meng, Fanle (Frontiers in Earth Science, 2024)
By using equipment such as time-lapse cameras and 3D laser scanners, this study conducted flume simulation experiments to obtain topographic elevation, the amount of sediment increment, sedimentary cross sections, and other related data and diagrams. Quantitative software was then utilized for sedimentological analysis to clarify the depositional evolution, architecture, and depositional model of lobate shallow-water deltas. The research results show that under the influence of hydraulic conditions and main distributary channels, lobate shallow-water deltas primarily undergo three evolution stages: initial channel formation, distributary channel system formation, and continuous stable evolution stage. The architecture elements of lobate shallow-water deltas can be divided into distributary channels dominated by channel deposition, proximal river mouth bars, transitional bars, and distal bars. The lateral composition and downstream deposition of the river-bar combination are the main structural units of the shallow water delta. The proximal profile distributary channels exist in the form of thick channel sand bodies with multiple repetitive intercalation cycles, and thick proximal bar deposits form on both sides of the distributary channels. The bifurcation of distributary channels in the middle profile leads to a reduction in channel scale, while large-scale proximal bars still develop on both sides of the channel. In the distal profile, a substantial river mouth bar complex is formed at the break of the delta front slope, and with the gradual progradation of the delta, the river mouth bar deposition zone becomes flattened. Based on the insights of the flume simulation experiments, a sedimentary model for lobate shallow-water delta was established.